Tłumaczenie wiersza klišej kliše Josipa Severa a zagadnienie muzyczności / The translation of Josip Sever`s poem klišej kiše (shutter of rain) and the question of musicality. - Ruttar, Anna (Przekłady Literatur Słowiańskich, 2009)
Does the musicality of the Josip Sever`s poem klišej kiše come through in the translation? The text Has the music gone from Josip Sever`s work? illustrates the influence of the translation process on textual levels of musicality: the sound sphere (consciously formed in relation to music) and making music a theme. It is mainly based on Polish post-war musico-literary studies, especially Andrzej Hejmej’s theory from the book Musicality of a literary work.